2015
DOI: 10.1519/jsc.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

Using a Verification Test for Determination of V[Combining Dot Above]O2max in Sedentary Adults With Obesity

Abstract: A constant-load exercise bout to exhaustion after a graded exercise test to verify maximal oxygen uptake (V[Combining Dot Above]O2max) during cycle ergometry has not been evaluated in sedentary adults with obesity. Nineteen sedentary men (n = 10) and women (n = 9) with obesity (age = 35.8 ± 8.6 years; body mass index [BMI] = 35.9 ± 5.1 kg·m; body fat percentage = 44.9 ± 7.2) performed a ramp-style maximal exercise test (ramp), followed by 5-10 minutes of active recovery, and then performed a constant-load exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 31 publications
6
75
3
Order By: Relevance
“…Using data from Poole et al (32), we estimated that a sample size of 16 participants would detect differences between incremental and verification tests at 80% power (α = 0.05; effect size = 0.759; two tailed hypothesis; based on a t test analysis) (15). The sample size of this study is comparable to other studies that have examined differences in V̇O 2 between incremental and verification tests (7, 22, 38) and to studies had have examined the validity of secondary criteria for establishing V̇O 2max (7, 32). All data were checked to ensure normal distribution.…”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…Using data from Poole et al (32), we estimated that a sample size of 16 participants would detect differences between incremental and verification tests at 80% power (α = 0.05; effect size = 0.759; two tailed hypothesis; based on a t test analysis) (15). The sample size of this study is comparable to other studies that have examined differences in V̇O 2 between incremental and verification tests (7, 22, 38) and to studies had have examined the validity of secondary criteria for establishing V̇O 2max (7, 32). All data were checked to ensure normal distribution.…”
Section: Methodsmentioning
confidence: 52%
“…In obese adults, a study by Sawyer et al (38) did not find significantly higher verification V̇O 2 when compared with incremental V̇O 2 , even though they did show substantial individual variability in the results with 13 out of 19 subjects achieving a V̇O 2 during verification testing that was 2 to 21% higher than the incremental test. The authors did not observe any relationship between BMI and performance on the verification test, which is consistent with the lack of differences between obese and nonobese groups in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…However, it should be noted that what is reported is group mean differences, which do not identify individuals who may not have attained a true normalV˙O2max. Using a larger sample size than in previous studies (n = 100), we found trueV˙normalO2 differences between GXT and VerT in the range of previous reports (2%‐3% ). However, upon identification of individuals with lower GXT the difference tripled.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in the literature evaluate the attainment of normalV˙O2max in obese individuals . The authors in two of these studies suggest that using verification test in obese sedentary adults may be useful and superior to secondary normalV˙O2max criteria . However, trueV˙normalO2 values during GXT and VerT were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation